Evaluation of antimicrobial activities of the crude extracts from Garcinia atroviridis and Solanum torvum - D.F, Basri; R, Sharif; P, Morat; J, Latip (Malaysian Journal of Science (MJS), 2005)
Crude ethyl acetate (EtOAc) and ethanol (EtOH) extracts from the fruits of Garcinia atroviridis and Solanum torvum were screened for their antimicrobial activities against 7 bacterial strains; 3 Gram-positive (Staphylococcus aureus ATCC 25923, S. epidemidis and Bacillus subtilis) and 4 Gram-negative bacteria (Escherichia coli 0157:H7, Salmonella typhimurium NCTC 74, S. enteritidis NCTC 5188 and Pseudomonas aeroginosa ATCC 27853) and 2 yeast strains (Candida glabrata and C. parapsilosis). Blank discs of 6 mm diameter were loaded with 10 mg/ml of the extracts applied to the inoculated plates. The results showed that the EtOAc and EtOH extracts from G. atrovoridis are active against all the microorganisms studied. Strongest inhibition zones were observed from EtOAc extract of Garcinia atroviridis against Staphylococcus epidemidis (25.27 ± 1.30 mm) and S. aureus (23.87 ± 1.10 mm) compared to positive control (Gentamycin at 10 µ/disc) with inhibition zones of 20.7 mm and 17.8 mm, respectively. Both the crude extracts from S. torvum displayed weak inhibitory effect against all Gram-positive bacteria tested. Among all the microorganisms in the study, S. enteritidis NCTC 5188, C. glabrata and C. parapsilosis were resistant towards the extracts from S. torvum.